Transcatheter Mitral Valve Repair for Functional Mitral Regurgitation: Evaluating the Evidence - Gelijns, Annetine C. (J Thorac Cardiovasc Surg, 2020)
OBJECTIVES: Two trials (COAPT and MITRA-FR) were published in 2018 evaluating the effectiveness and safety of transcatheter repair for heart failure patients with significant functional MR, which yielded different results. This paper reviews the strength of the evidence, differences in trial designs, ethical and implementation implications, and delineates future research needs to help guide the appropriate dissemination of transcatheter repair for functional MR patients. METHODS: The National Heart, Lung and Blood Institute convened a workshop of interdisciplinary experts to address these objectives. RESULTS: Transcatheter repair of functional MR can provide significant benefits in terms of heart failure hospitalizations, survival and quality-of-life, when appropriate heart failure candidates, with moderate to severe or severe MR while on optimal guideline-directed medical therapy, can be identified. Key ingredients for success are pre-operative evaluation and management and post-operative care by an interdisciplinary heart team. CONCLUSIONS: Given the discordance observed between trials, ongoing innovation in patient management and potential expansion of indications for use, the evidence base must be expanded to optimize appropriate implementation of this complex therapy. This will require more complete capture of outcome data in real-world settings for all eligible candidates, whether or not they receive this therapy. Inevitably, the indications for use of this therapy will expand, as will the devices and therapeutic approaches for this population, necessitating the study of comparative effectiveness through randomized trials or observational studies. Moreover, given the substantial variations in care delivery, conducting implementation research to delineate characteristics of the optimal care model would be of benefit.